Pengaruh Self-Efficacy terhadap Kinerja Melalui Kepuasan Kerja Sebagai Variabel Intervening (Study Pada Karyawan UD Indah Collection) - Nur Siamita; Iriani Ismail (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
The purposes of this studyare: 1) To determine whether self-efficacy has a positive and  significant  effect onemployees performance 2) To determine whether Self-efficacy has a positive and significant effect on job satisfaction 3) To determine whether job satisfaction has a positive and significant effect on  employees performance, 4) To  determine whether  Self-efficacy  have a positive and significant effect on employees performance through job satisfaction as an intervening variable. Based on path analysis, it found that Self-efficacy has a positive and significant effect on employees performance with a standardized coefficients betais 0.432 or 43.2%,  Self-efficacy has a positive and significant effect on job satisfaction with a beta standardized coefficients value is 0.857 or 85, 7%, Job satisfaction has a positive and significant effect on employees performance with a standardized coefficients beta value is 0.534 or 53.4%,  Self-efficacy has a positive and significant effect on   employees  performance  through   job  satisfaction  as  an  intervening variable by the value of standardized coefficients beta (self-efficacy on employees performance)and the effect of self-efficacy on job satisfaction is 0.857 x 0.534 = 0.457 or 45.7%.